2007
DOI: 10.7202/016190ar
|View full text |Cite
|
Sign up to set email alerts
|

Une analyse des écrits sur les impacts du jeu sur l’apprentissage

Abstract: Cet article présente une synthèse des publications récentes (1998-2005) qui traitent des impacts du jeu, en tant que formule pédagogique, sur l’apprentissage. Constatant une grande variété d’approches, une certaine disparité dans la manière de présenter et d’interpréter les résultats, et souhaitant vérifier si les jeux éducatifs ont un impact réel sur l’apprentissage, les auteurs ont procédé à une recension des écrits sur le sujet à partir d’une grille d’analyse validée. Ces impacts sont détaillés après un rés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 51 publications
(27 reference statements)
0
9
0
7
Order By: Relevance
“…They follow a constructivist logic in which the players build their own knowledge by confronting a problem in a simulated world. A meta-analysis gathering 193 articles about serious games [8] has shown the following benefits: favouring the development of social and human relationships and communication skills; increasing learning motivation, self-esteem and self-confidence, engagement and persistence; developing problem-solving skills; helping learners to structure, build and represent knowledge; and helping learners to integrate information by developing the capability to build links and transfer knowledge from other contexts.…”
Section: Serious Games For Teachingmentioning
confidence: 99%
“…They follow a constructivist logic in which the players build their own knowledge by confronting a problem in a simulated world. A meta-analysis gathering 193 articles about serious games [8] has shown the following benefits: favouring the development of social and human relationships and communication skills; increasing learning motivation, self-esteem and self-confidence, engagement and persistence; developing problem-solving skills; helping learners to structure, build and represent knowledge; and helping learners to integrate information by developing the capability to build links and transfer knowledge from other contexts.…”
Section: Serious Games For Teachingmentioning
confidence: 99%
“…The use of educational and interactive games and cartoons as well are good ways to poke the interest of and to promote long-term information retention. (4). In India a study had shown that exposing school children to different health education activities such as live demonstrations, and slide shows when both events were grouped a high average of correct score (47.88%) in comparison to that of control group (26.56%) (5).…”
Section: Discussionmentioning
confidence: 99%
“…Dentre as plataformas que disponibilizam jogos com fins educacionais, destacam-se o Moodle e o EGC-SAVIE [Sauvé et al 2005]. A plataforma Moodle (Modular Object-Oriented Dynamic Learning Environment), através do módulo Moodle Game, provê jogos aos seus usuários, mas a busca é meramente sintática.…”
Section: Discussionunclassified
“…Contudo, quando o modelo da literatura encontrado faz busca e recuperação semântica de objetos de aprendizagem (considerando que uma AA-Jogo pode ser vista como um objeto de aprendizagem), a preocupação dos seus desenvolvedores é em organizar melhor o domínio do conteúdo e do armazenamento dos objetos de aprendizagem, mas sem tratar especificamente de jogos educacionais [Campos et al, 2011;Araujo et al, 2011]; quando o modelo da literatura trata de jogos educacionais, oferecem apenas mecanismo de busca sintática de jogos [Moodle, 2012;Sauvé et al, 2005]. Em ambos os casos, nenhum desses modelos considera importante modelar o contexto da atividade de aprendizagem para obter jogos mais apropriados a esse contexto.…”
Section: Introductionunclassified